Gene Mutation as Biomarker of Radiation Induced Cell Injury and Genomic Instability - M Syaifudin (PPIKSN-BATAN, 2006)
Gene expression profiling and its mutation has become one of the most widely used approaches to identify genes and their functions in the context of identify and categorize genes to be used as radiation effect markers including cell and tissue sensitivities. Ionizing radiation produces genetic damage and changes in gene expression that may lead to cancer due to specific protein that controlling cell proliferation altered the function, its expression or both. P53 protein encoded by p53 gene plays an important role in protecting cell by inducing growth arrest and or cell suicide (apoptosis) after deoxyribonucleic acid (DNA) damage induced by mutagen such as ionizing radiation. The mutant and thereby dysfunctional of this gene was found in more than 50% of various human cancers, but it is as yet unclear how p53 mutations lead to neoplastic development. Wild-type p53 has been postulated to play a role in DNA repair, suggesting that expression of mutant forms of p53 might alter cellular resistance to the DNA damage caused by radiation. Moreover, p53 is thought to function as a cell cycle checkpoint after irradiation, also suggesting that mutant p53 might change the cellular proliferative response to radiation. p53 mutations affect the cellular response to DNA damage, either by increasing DNA repair processes or, possibly, by increasing cellular tolerance to DNA damage. The association of p53 mutations with increased radioresistance suggests that alterations in the p53 gene might lead to oncogenic transformation. Current attractive model of carcinogenesis also showed that p53 gene is the major target of radiation. The majority of p53 mutations found so far is single base pairchanges (point mutations), which result in amino acid substitutionsor truncated forms of the P53 protein, and are widely distributedthroughout the evolutionarily conserved regions of the gene. Examination of p53 mutations in human cancer also shows an association between particular carcinogens and characteristicpatterns of these mutations. Even amongcancers of the same organ, the mutational spectrum of the p53gene could present different patterns by histologic subtypeor risk factors and mutagen involved